Implications Of The Glasgow Agreement (Cop26) Phasing-Down Of Unabated Coal Power On Indonesia's Trade Balance - Yulianto, Ivan; Subiyantoro, Heru (Pusat Publikasi Nusantara, 2023)
ABSTRACT At the 26th annual United Nations climate change conference (COP26) in Glasgow, Scotland, 197 countries succeeded in reaching an agreement to address the “Phase-down of Unabated Coal Power”, i.e. the gradual reduction of coal-fired power generation and to ends fossil fuel subsidies that are not in efficient. Its going with the policy of Indonesia Government, in the General Draft of National Energy (RUEN), they will limit coal production up to 400 million tons per year and the exports will be reduced gradually from year to year and will be stopped on 2046. In another hand, China and India's dependence on coal energy for power generation and industry is still very high. Both countries demanding will affect Indonesia's trade balance considering the proportion of Indonesia's coal exports is 71% compared to domestic consumption. To determine this effect, this study uses the Autoregression Vector (VAR) model with annual data from 2000 to 2021. The test results show that Indonesia's coal exports have an effect on the trade balance by 13.17% in terms of the total export value. International coal price will have a positive impact on the Indonesia’s trade balance by 17.91%. However, the price of coal is very influential on the volume of Indonesia’s coal export. Momentum of Phase-down Coal is a golden opportunity to maximize economic benefits while preparing renewable energy as a substitute for coal.